Mothers' knowledge before and after receiving education about baby massage in the workplace - Juliana, Enggar; Yulianti, Emy; Damayanti, Dini Fitri (Borneo Scientific Publishing, 2024)
Baby massage is a form of comfortable communication between mothers and infants that provides health benefits, including supporting weight gain. A preliminary study showed that mothers’ awareness and practice of baby massage were still low, and the procedure was mostly performed by traditional healers. This study aimed to analyze the difference in mothers’ knowledge before and after receiving counseling on baby massage in the working area of the Perumnas II Pontianak Community Health Center. Using a pre-experimental one-group pre-test–post-test design, this study involved 30 respondents selected through consecutive sampling, and data were analyzed using the Wilcoxon test. The results showed a significant increase in mothers’ knowledge after counseling (p = 0.000). In conclusion, counseling on baby massage effectively improved maternal knowledge and is recommended as a health education strategy in community settings.